Implementasi Katekese Model Shared Christian Praxis Untuk Meningkatkan Keterlibatan Orang Muda Katolik Di Stasi Santo Yohanes Rasul Rawa Biru - Kabujai, Fitalia Yadao; Pranyoto, Yohanes Hendro; Berangka, Dedimus (STPK St. Yohanes Rasul Jayapura, 2025)
This study aims to examine the implementation of the Shared Christian Praxis (SCP) catechesis model to enhance Catholic Youth (OMK) involvement in church life at St. John the Apostle Station Rawa Biru. The low participation of OMK (only 15% of 40 active members) serves as the research background. A qualitative method with participatory action research design was employed through observation, in-depth interviews with 6 informants, and documentation of catechesis implementation. Thomas Groome's SCP model was applied in two meetings with relevant themes. Research findings reveal three factors causing low involvement: economic (priority on livelihood as the dominant factor), internal (lack of motivation and self-confidence), and external (minimal family support and absence of structured formation). SCP implementation received positive responses despite limited participation. Participants showed progression from passive attitudes to greater openness in sharing experiences. The SCP model effectively increased Christian identity awareness, self-confidence, and involvement commitment, although its impact remains limited. The research concludes that the SCP model proves effective but requires systemic support and long-term consistency. This model offers a contextual and participatory catechesis alternative, integrating life experiences with faith traditions. Recommendations include developing holistic pastoral programs, enhancing local catechist capacity, and strengthening multi-level accompaniment systems.